Trauma patient transport to hospital using helicopter emergency medical services or road ambulance in Sweden: a comparison of survival and prehospital time intervals - Oscar Lapidus; Rebecka Rubenson Wahlin; Denise Bäckström (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2023)
Abstract Background The benefits of helicopter emergency medical services (HEMS) transport of adults following major trauma have been examined with mixed results, with some studies reporting a survival benefit compared to regular emergency medical services (EMS). The benefit of HEMS in the context of the Swedish trauma system remains unclear. Aim To investigate differences in survival and prehospital time intervals for trauma patients in Sweden transported by HEMS compared to road ambulance EMS. Methods A total of 74,032 trauma patients treated during 2012–2022 were identified through the Swedish Trauma Registry (SweTrau). The primary outcome was 30-day mortality and Glasgow Outcome Score at discharge from hospital (to home or rehab); secondary outcomes were the proportion of severely injured patients who triggered a trauma team activation (TTA) on arrival to hospital and the proportion of severely injured patients with GCS ≤ 8 who were subject to prehospital endotracheal intubation. Results 4529 out of 74,032 patients were transported by HEMS during the study period. HEMS patients had significantly lower mortality compared to patients transported by EMS at 1.9% vs 4.3% (ISS 9–15), 5.4% vs 9.4% (ISS 16–24) and 31% vs 42% (ISS ≥ 25) (p < 0.001). Transport by HEMS was also associated with worse neurological outcome at discharge from hospital, as well as a higher rate of in-hospital TTA for severely injured patients and higher rate of prehospital intubation for severely injured patients with GCS ≤ 8. Prehospital time intervals were significantly longer for HEMS patients compared to EMS across all injury severity groups. Conclusion Trauma patients transported to hospital by HEMS had significantly lower mortality compared to those transported by EMS, despite longer prehospital time intervals and greater injury severity. However, this survival benefit may have been at the expense of a higher degree of adverse neurological outcome. Increasing the availability of HEMS to include all regions should be considered as it may be the preferrable option for transport of severely injured trauma patients in Sweden.